Pengaruh Pendidikan Kewirausahaan dan Motivasi Berwirausaha Terhadap Minat Berwirausaha dengan Self-Efficacy sebagai Variabel Intervening: Studi pada Siswa SMK Darut Taqwa Sengonagung Purwosari Pasuruan - Maslikhatul Uriva Chuswanto; Nur Rohmad Nuzil (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The author's background is the level of interest in entrepreneurship as seen throughentrepreneurship education, entrepreneurship motivation and self-efficacy, all of whichhave not been categorized as good and meet the entrepreneurship interests of students atDarut Taqwa Sengonagung Vocational School. The formulation of the problem in thisresearch is how entrepreneurship education, entrepreneurial motivation influencesinterest in entrepreneurship through self-efficacy in Darut Taqwa SengonagungVocational School students.The aim of this research is to determine and analyze entrepreneurial educationvariables, entrepreneurial motivation which influences interest in entrepreneurshipthrough self-efficacy in Darut Taqwa Sengonagung Vocational School students.This research was conducted to determine "The influence of entrepreneurshipeducation, entrepreneurial motivation influences interest in entrepreneurship throughself-efficacy as an intervening study variable for students at Darut Taqwa SengonagungVocational School." The strategy used in this research is causal associative research witha quantitative approach, with questionnaires distributed as a collection technique. data.The sampling method uses purposive sampling, namely a sampling technique wherepeople are selected as samples according to the purpose of the research. The sample usedwas 105 respondents through distributing questionnaires. The data analysis method usedin this research is Linear Explanatory. The results of the research state that the variablesEntrepreneurship Education and Self Efficacy have a negative and insignificant effecton Entrepreneurial Interest, while Entrepreneurial Motivation has a positive andsignificant effect on Entrepreneurial Interest.